Gastric perforation induced by non-steroidal anti-inflammatory drugs: a case report - Arrieta Navarro, Julio Caleb (2025)
Gastric perforation is a serious and potentially fatal complication of prolonged or improper use of non-steroidal anti-inflammatory drugs (NSAIDs). Their primary mechanism involves the inhibition of prostaglandin synthesis, which reduces mucosal protection and promotes the formation of ulcers susceptible to perforation. We report the case of a 30-year-old male who, after taking etoricoxib and then self-medicating with diclofenac for two weeks, developed progressive colicky abdominal pain along with nausea and general malaise. One day prior to admission, the pain suddenly became persistent and severe, accompanied by vomiting, abdominal distension, sweating (diaphoresis), and shortness of breath (dyspnea). On examination, he had a distended abdomen, a positive Blumberg sign (rebound tenderness), and severe epigastric pain. An X-ray showed pneumoperitoneum (air in the abdominal cavity), prompting emergency laparotomy, which revealed a 0.5 cm perforation on the anterior wall of the pylorus. Early intervention prevented peritonitis and septic shock. This case demonstrates that prompt clinical and imaging assessments are crucial for effective management and highlights the importance of education about self-medication to prevent fatal outcomes.